The Myth of Rain in Wedding Ceremonies Jambak Tribe Community in Nagari Canduang Koto Laweh - Alfarezi, Muhammad; Endrizal, Endrizal; Septriani, Septriani (Kirana Publisher (KNPub), 2024)
This research discusses